Harmonizing Commercial and Investment Arbitration: Conflict Dynamics - Vasudevan , Jaya (Journal of Sustainable Development Law and Policy, 2025)
This article provides an independent analysis of the scope and extent of arbitration under investment agreements, and the implications of the possible convergence in the process of harmonization of international commercial arbitration law. The successful settlement of any dispute depends on the compatibility of the nature of the dispute with the technique to which it is submitted for resolution. In the last decade, there was a constant increase in the number of disputes that were subjected to arbitration and a major chunk of those disputes covered a comparatively new but known area called international investment law. With economic globalization allowing the free flow of foreign direct investment (FDI) in and out of a country, the existing regulatory framework in international law to standardize investment liberalization is often seen as ineffective, hence the consequent disputes. Here, arbitration offers a suitable framework for the amicable settlement of commercial disputes covering investment agreements with the assistance of bilateral or multilateral agreements between the states. Preferential trade agreements pertaining to investment often contain an arbitration clause for the settlement of future disputes between parties. At this juncture, one may find that there exists a fundamental dilemma in ascertaining the true nature of investment arbitration and how it is different from commercial arbitration. For example, the protection being offered to human rights under the purview of investment arbitration may generate doubts in the minds of investment arbitrators. In commercial arbitration, divergences in a pluralistic order become particularly relevant whereas the diverse legal cultures supported by individual constitutional frameworks have a direct impact on investment arbitration due to their practical application. The article also discusses the need for harmonized rules governing arbitration procedures while maintaining the functional dissimilarities between commercial and investment arbitration.